PENINGKATAN WEBSITE RANKING EXIST-CLUB PADA PB EXIST JAKARTA - Untung Rahardja; Khanna Tiara; Imam Prayogi (CCIT Journal, 2015)
One of the technologies developed in the increasingly computerized world of information technology is the website. The website is an information media offers a range of up to date information and the existence of a good maintenance process, evena role in website ranking positions should be also of note because it is one of thenecessities in the present information especially in the sport of badminton. This has been the rationale for how to improve the position of web rank significantly in order topopularize a Website Exist-Club which is the official website of PB Exist a badminton clublocated in Jakarta so that it can affect the visitor traffic of visitors is high. The speed andconvenience of a positive value in a website with so will make it easier to access by anyone and anywhere. To accomplish the intended, there are 17 step strategyimplemented for the purpose of improving the web rank Websites Exist-Club which willdirectly account for direct pembuktiannya on a measuring instrument using the Alexa and Google Analytics.